High-Risk Esophageal GIST: Imaging and Therapeutic Impact on Atypical Metastatic Lesions - Predrag Sabljak; Aleksandra Djuric-Stefanovic; Miljana Bubanja; Strahinja Odalovic; Nenad Ivanovic; Milica Mitrovic-Jovanovic; Ognjan Skrobic (Diagnostics)
This case represents a relatively rare localization of a gastrointestinal stromal tumor involving the distal esophagus with a very unusual mode of metastatic spread to the lymph nodes and bone structures. Diagnostic follow-up showed the effect of tyrosine kinase inhibitor therapy on metastatic lesions, highlighting the necessity of comprehensive diagnostic evaluation in patients with atypical presentations and contributing to the improvement of therapeutic strategies in complex clinical scenarios.